Lung Sarcomatoid Carcinoma Metastasis to Skin: A Case Report and Review of the Literature. (2nd July 2016) - Xu, Xuezhu; Lin, Mao; Wang, Shengyi; Jin, Zeyu; Han, Shixin; Liu, Xia; Gao, Yuxue
ABSTRACT: Sarcomatoid carcinoma is a biphasic neoplasm composed of highly complex, intimately admixed malignant epithelial and mesenchymal elements. We herein report a rare case of cutaneous metastasis of pulmonary sarcomatoid carcinoma that contains liposarcomatous, rhabdosarcomatous and chondrosarcomatous heterologous differentiation, and review relevant literatures to lead to a better understanding of this rare but highly aggressive tumor.